QUANTIFICATION OF WATER CONTENT AND SPECIATION IN NATURAL SILICIC GLASSES (PHONOLITE, DACITE, RHYOLITE) BY CONFOCAL MICRORAMAN SPECTROMETRY - Di Muro A.; Villemant B.; Montagnac G.; Scaillet B.; Reynard B. (My University, 2006)
The determination of total water content (H2OT: 0.1-10 wt%) and water speciation (H2Omolecular/OH) in volcanic products by confocal microRaman spectrometry are discussed for alkaline (phonolite) and calcalkaline (dacite and rhyolite) silicic glasses. Shape and spectral distribution of the total water band (H2OT) at ?3550 cm-1 show systematic evolution with glass H2OT, water speciation and NBO/T. In the studied set of silicic samples, calibrations based on internal normalization of the H2OT band to a band related to vibration of aluminosilicate network (TOT) at ?490 cm-1 vary with glass peraluminosity. An external calibration procedure using well-characterized glass standards is less composition-dependent and provides excellent linear correlation between total dissolved water content and height or area of the H2OT Raman band. Accuracy of deconvolution procedure of the H2OT band to quantify water speciation in water-rich and depolymerized glasses depends on the strength of OH hydrogen bonding. System confocal performance, scattering from embedding medium and glass microcrystallinity have a crucial influence on accuracy of Raman analyses of water content in glass-bearing rocks and melt inclusions in crystals. ? 2006 Elsevier Inc. All rights reserved.
Keywords: DACITE; PHONOLITE; RAMAN SPECTROSCOPY; RHYOLITE; SPECIATION (CHEMISTRY); WATER CONTENT